COMPARATIVE ANALYSIS OF RECURRENT EPITHELIZED PILONIDAL SINUS AND SACROCOCCYGEALFISTULAS TREATMENT - Z. K. Magomedova; E. V. Chernyshova; V. S. Groshilin (Медицинский вестник Юга России, 2015)
Purpose: to improve the results of surgical treatment in patients with epithelized pilonidal sinus (EPS) by developing and incalcating an effective surgical method comprising measures for preventing recurrence.Materials and methods: 60 patients with EPS and sacrococcygeal fistulas have been operated, of the total number of 60,in 22 patients EPS excision was followed by suturing the wound edges to the bottom; in 10 patients the wounds were left open, in 9 excision supplemented bywound defect plastics with displaced non-free skin flaps in the developed modifications.The choice of operation method depended on the extent of the inflammatory process, duration of the disease, a history of recurrence.Results: 3 cases of recurrence (30%) were registered in the I group of patients; 7 cases of recurrence(31,8%) – in the II group; 4 cases of recurrence (44., %) – in the III group; 3 cases of recurrence (15,8 %) - in the IV group.Conclusion: radical surgery with simultaneous closure of the surgical wound with non-free skin flapsare the most promising for improving long-term results in EPS treatment (including recurrent fistulas), as evidenced by the immediate and long-term results.Key words: epithelized pilonidal sinus, plastic counter flaps, pilonidal cyst, suppuration, recurrence.